2018
DOI: 10.3892/ijo.2018.4376
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced autophagy promotes gemcitabine resistance in human bladder cancer cells through hypoxia-inducible factor 1α activation

Abstract: Overcoming the chemoresistance of bladder cancer is a pivotal obstacle in clinical treatments. Hypoxia widely exists in solid tumors and has been demonstrated to contribute to chemoresistance through hypoxia-inducible factor 1α (HIF‑1α)-mediated autophagy in several types of cancer. However, it is unclear whether HIF‑1α-mediated autophagy and chemoresistance occur in bladder cancer. The present study demonstrated that HIF‑1α was overexpressed in 20 bladder cancer tissues compared with matched paracarcinoma tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 45 publications
6
43
0
Order By: Relevance
“…Hypoxia was found to inhibit cisplatin‐induced apoptosis in ovarian cancer cells and enhance chemoresistance to cisplatin . In bladder cancer cells, hypoxia was found to activate autophagy and significantly reduce gemcitabine‐induced apoptosis compared with normoxic conditions . In agreement with our findings, gemcitabine cytotoxicity was increased in bladder cancer cells when combined with the autophagy inhibitor 3‐MA.…”
Section: Discussionsupporting
confidence: 91%
“…Hypoxia was found to inhibit cisplatin‐induced apoptosis in ovarian cancer cells and enhance chemoresistance to cisplatin . In bladder cancer cells, hypoxia was found to activate autophagy and significantly reduce gemcitabine‐induced apoptosis compared with normoxic conditions . In agreement with our findings, gemcitabine cytotoxicity was increased in bladder cancer cells when combined with the autophagy inhibitor 3‐MA.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have reported that UVRAG not only promotes Beclin‐1‐mediated autophagy, but it also facilitates endosome/autophagosome maturation . Activation of autophagy can increase chemo‐ and radiotherapy resistance in bladder cancer . We also found that high expression of UVRAG predicted poor prognosis, which was consistent with the role of circUVRAG.…”
Section: Discussionsupporting
confidence: 86%
“…18,19 Activation of autophagy can increase chemo-and radiotherapy resistance in bladder cancer. [20][21][22] We also found that high expression of UVRAG predicted poor prognosis, which was consistent with the role of circUVRAG.…”
Section: Discussionsupporting
confidence: 85%
“…Autophagy, which is a mechanism of cellular degradation through lysosomes, is also involved in a HIF-1α-mediated cell survival mechanism (8,9). Hypoxia-induced autophagy can lead to chemoresistance and malignant progression of cancer cells (10). Therefore, suppression of hypoxia-induced autophagy may help inhibit the tumorigenesis of glioblastoma.…”
Section: Introductionmentioning
confidence: 99%